A function to provide neutron spectrum produced from the 9Be + p reaction with protons of energy below 12 MeV. Issue 8 (3rd August 2018) - Wakabayashi, Yasuo; Taketani, Atsushi; Hashiguchi, Takao; Ikeda, Yoshimasa; Kobayashi, Tomohiro; Wang, Sheng; Yan, Mingfei; Harada, Masahide; Ikeda, Yujiro; Otake, Yoshie
ABSTRACT: A function to give the total neutron production cross section, angular distribution, and energy spectrum via the 9 Be + p reaction has been created by fitting experimental data to characterize compact neutron sources with thick Be targets bombarded by protons with energy below 12 MeV. To examine the suitability of the function, calculations of the angle-dependent neutron energy spectra produced in thick Be targets with 4- and 12-MeV protons using the function were compared with corresponding experiments and calculations using the nuclear data libraries of ENDF/B-VII.0 and JENDL4.0/HE. The function was in better agreement with the experiments than the calculations using the libraries except for at backward angles. The 115 In(n, n') 115m In reaction rates calculated using GEANT4 with source neutrons given by both the function and ENDF/B-VII.0 were compared with that measured at the RIKEN Accelerator-Driven Compact Neutron Source to evaluate the neutron spectrum above 1 MeV. The function slightly overestimated the measurement by 14% and the calculation with ENDF/B-VII.0 underestimated by 35%. It was concluded that the function can be applied in compact neutron source designs.